Reengineering the relationship between tax knowledge and voluntary tax compliance in nigeria: the moderating role of tax service quality - Yahaya, Lawan (Human Resource Management Academic Research Society, 2023)
The purpose of this study is to examine the moderating role of tax service quality on the relationships between tax knowledge and voluntary tax compliance in Nigeria. The study used partial least squares structural equation modeling (SEM SmartPLS 3.3) to analyze the direct and moderating effect based on 296 self-employed taxpayers in Nigeria. The result indicates a negative and insignificant direct effect between tax knowledge and voluntary tax compliance. The finding further reveals that tax service quality has a positive and significant effect with voluntary tax compliance. Whereas tax service quality significantly moderates the relationship between tax knowledge and voluntary tax compliance. The results show that a mixed combination of tax knowledge and tax service quality can lead to improved tax compliance. Our results contribute to the previous studies that have largely examined the direct relationship between tax knowledge and tax compliance by signifying that tax service quality moderate the relationship between tax knowledge and voluntary tax compliance. The study recommends frequent awareness and educating the taxpayers on the relevance of tax knowledge and providing quality of tax service to improve voluntary tax compliance.